Relasi Gerakan Aceh Merdeka (GAM), Masyarakat dan TNI - Polri dalam Pandangan Antropologi Kepolisian - Bakharuddin Muhammad Syah (Syntax Corporation Indonesia, 2024)
Aceh has a rich history of culture, but its history is also filled with events that shook the society. One of them is the Free Aceh Movement (GAM), which attracted the attention of not only the Indonesian people, but also the government and authoritarian parties (TNI-POLRI). The Free Aceh Movement has been analyzed and has a considerable literature review. GAM is also a topic that is often looked at by academics to analyze the events of the movement as a social phenomenon. In this paper, the authors approach GAM as an anthropological policing phenomenon through the lens of the theory. To compare with other studies, the authors also collected various literatures as a basis for analysis and as an instrument to strengthen the argument.